PENGARUH LINGKUNGAN KERJA DAN KREATIVITAS TERHADAP STRES GURU SMA NEGERI SUB RAYON 1 KOTA BEKASI - Wati Hernawati (Jurnal Manajemen Pendidikan, 2013)
The objective of this research was to determine the Effect of Work Environment and Creativity to the Stress of Teacher at Junior High School in Medan Satria Bekasi.The data were collected through participant observation using survey by questionnaires. The data analysis using simple correlation, simple linear regression. Tlie target population size of this research is 236 teachers. Research samples selected as much as 149 teachers using simple random sampling technique.Tlie data obtained analyzed using path analysis technique. Based on this research of data obtained the following conclusions: (1) the work environment have negative direct effect to stress, (2) the creativity have negative direct effect to work stress, (3) the work environment have positive direct effect to creativity.